INVENTARIO DE MOLUSCOS EN EL INFRALITORAL DE HUANCHACO- LA LIBERTAD, ENERO A JULIO 2013. - Flores León, Lorenzo Jesús (2013)
The inventory of molluscs in the infralittoral of Huanchaco from january to july 2013_x000D_ was performed. The Samples were collected every fifteen days in eight spots_x000D_ georeferenced located in an area between the 08 o 04 '46,42 "- 08 ° 04' 37,37" Sto_x000D_ 79° 07 '23,54 "- 79 ° 07' 13,78" W, with a grid of 1 m2 during low tides by apnea_x000D_ diving and species were identified using taxonomic keys and shellfish reports. were_x000D_ recorded 17 species, nine Gastropoda species and eight Polyplacophora, of which 12_x000D_ were Huanchaco coast new records. Five species belong to the class Gastropoda:_x000D_ Fissurella pulchra, Fissurella sp., Crepipatella dilatata, Stramonita biserialis and_x000D_ Crassilabrum crassilabrum, and seven belong to the class Polyplacophora:_x000D_ Acanthopleura echinata, Chiton granosus, Tonicia chilensis, Chiton sp.,_x000D_ Chaetopleura sp.l, Chaetopleura sp.2 and Chaetopleura sp.3. The species with the_x000D_ highest density (ind/m2 ) were Prisogaster niger, Tegula atra and Chiton cumingsii_x000D_ with over 30 ind/m2 • It was determined that the largest number of species was class_x000D_ Gastropoda, and also noted that in march saw the highest number of species (12).